The Decision to Bring a Judge to Disciplinary Responsibility as a Civil-Procedural Ground for the Review of Judicial Act due to New Circumstance - Hovhannisyan, V. (Bulletin of Yerevan University C: Jurisprudence, 2017)
Complete and effective functioning of judicial power presumes securing of such guarantees in RA legal system, that are in their maximum intended to the realization of tasks arising from constitutional – legal status of courts and judges and will ensure the main qualitative parameters of justice administration, independence of judicial system, as well as effective protection of rights and legal interests of civil process participants. The article discusses possible legal consequences arising in civil procedure as a result of a decision adopted in line with the procedure provided by Constitution in regard imposing legal sanctions towards a judge who either has committed violations during justice administration or not performed or improperly performed his/her consitutional obligations or abused them. The author concludes, that based on the need of full realization of parties’ rights to fair trial and judicial protection, the Council’s acknowledgment of the fact of clear and grave breach of material or procedural legal norm instead of an adopted decision by the Council to bring a judge to disciplinary responsibility shall serve as the basis for revision of judicial act. It is proposed to amend part 3 of the article 204.22 of the RA Code of Civil Procedure accordingly.